Deficits in Dynamic Balance and Hop Performance Following ACL Reconstruction Are Not Dependent on Meniscal Injury History - Adam VanZile; Malcolm Driessen; Patrick Grabowski; Hanni Cowley; Thomas Almonroeder (North American Sports Medicine Institute, 2022)
# Background Athletes often exhibit persistent deficits in dynamic balance and hop performance in their involved limb following ACL reconstruction. However, it is unclear how meniscal injury history affects inter-limb asymmetry. # Purpose The purpose of this study was to compare inter-limb asymmetry in dynamic balance and hop performance in athletes with and without a history of concomitant meniscal injury. # Study Design Cross-sectional study # Methods Dynamic balance and hop test data were analyzed for 34 adolescent athletes who had undergone ACL reconstruction; 19 athletes had sustained an isolated ACL tear, while 15 had sustained an ACL tear along with a meniscus injury. Athletes who had sustained a meniscus injury were sub-divided into those who underwent a meniscal repair (n = 9) versus a partial meniscectomy (n = 6). Dynamic balance was assessed using the Y-Balance Test, while hop performance was assessed using the single and triple hop tests. Data were recorded at the time of return-to-sport testing (5-11 months post-surgery). For each variable, mixed-model analysis of variance, with a between-subjects factor of group (isolated ACL tear, meniscal repair, partial meniscectomy) and a within-subjects factor of limb (involved, uninvolved), was conducted. # Results The groups exhibited similar degrees of inter-limb asymmetry in dynamic balance and hop test performance, as there was not a group-by-limb interaction effect for the Y-Balance Test distances (p ≥ 0.43) or hop test distances (p ≥ 0.96). However, there was a main effect of limb for the anterior and posteromedial Y-Balance Test distances and the single and triple hop test distances (p ≤ 0.004). For each variable, performance was worse for the involved limb, compared to the uninvolved limb. # Conclusion It appears that deficits in dynamic balance and hop performance among adolescent athletes who have undergone ACL reconstruction are not dependent on meniscal injury/surgery history. # Level of Evidence 3